The multiple meanings of ADHD: between deficit, disruption and hidden potential - Aude Béliard; Álvaro Jiménez-Molina; Javiera Díaz-Valdés; Alice Le Goff; Sarra Mougel; Hugo Sir
Abstract The purpose of this article is to describe the subjective experience of the diagnosis of Attention Deficit and Hyperactivity Disorder (ADHD) and the cultural meanings that shape this experience. Based on interviews and discussion groups with diagnosed people and their families in Chile and France, this article show that ADHD can acquire multiple meanings. From a thematic analysis, we identified three registers or ways of living and thinking about ADHD. In the deficit register, the disorder is experienced primarily as a failure of certain abilities. In the disruption register, the disorder is experienced as disrupting the person's life, personality and interactions, which must then be normalized. In the register of hidden potential, on which this article focuses, ADHD is simultaneously thought of as a difficult and valuable condition, a source of exceptional capacities that are often hidden in the ordinary functioning of social life. We therefore invite reflection that identifies the factors of mobilization or non-mobilization of the hidden potential register, with particular emphasis not only on relational configurations, socio-economic variables, and the gender variable, but also on the institutional and political context of each country.